On the intermolecular Coulombic decay of singly and doubly ionized states of water dimer - Stoychev, Spas Dimitrov; Kuleff, Alexander I.; Cederbaum, Lorenz S. (The journal of chemical physics, 2010)
A semiquantitative study of the intermolecular Coulombic decay (ICD) of singly and doubly ionized water dimer has been carried out with the help of ab initio computed ionization spectra and potential energy curves (PECs). These PECs are particular cuts through the (H2O)2, (H2O)2+, and (H2O)2 hypersurfaces along the distance between the two oxygen atoms. A comparison with the recently published experimental data for the ICD in singly ionized water dimers [T. Jahnke, H. Sann, T. Havermeier et al., Nat. Phys. 6, 139 (2010)] and in large water clusters [M. Mucke, M. Braune, S. Barth et al., Nat. Phys. 6, 143 (2010)] shows that such a simplified description in which the internal degrees of freedom of the water molecules are frozen gives surprisingly useful results. Other possible decay channels of the singly ionized water dimer are also investigated and the influence of the H-atom participating in the hydrogen bond on the spectra of the proton-donor and proton-acceptor molecules in the dimer is discussed. Importantly, the decay processes of one-site dicationic states of water dimer are discussed and an estimate of the ICD-electron spectra is made. More than 33% of the dications produced by Auger decay are found to undergo ICD. The qualitative results show that the ICD following Auger decay in water is also expected to be an additional source of low-energy electrons proven to be extremely important for causing damages to living tissues.
Gesehen am 28.08.2023